2015
DOI: 10.1142/s2339547815400105
|View full text |Cite
|
Sign up to set email alerts
|

An economic analysis of bioethanol production from the marine macroalga Ulva (Chlorophyta)

Abstract: We performed a cost-benefit analysis for bioethanol production using biomass of Ulva rigida, a marine macroalga (seaweed), co-cultured with fish in an intensive offshore aquaculture unit. This is the first report for such analysis that takes into consideration offshore seaweed cultivation and uses a recently developed, novel and simplified ethanol production technology that is devoid of costly pre-treatments imposed to the seaweed biomass. By simultaneously producing ethanol with valuable Dried Distillers Grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…was chosen as the model species as it is very common on the shores of Israel and displayed high biomass productivity in extensive cultivation offshore in Israeli waters . Furthermore, the production of proteins and starch, and biomass fermentation to acetone, ethanol, butanol, and polyhydroxyalkanoates from several Ulva species has already been demonstrated …”
Section: Introductionmentioning
confidence: 76%
“…was chosen as the model species as it is very common on the shores of Israel and displayed high biomass productivity in extensive cultivation offshore in Israeli waters . Furthermore, the production of proteins and starch, and biomass fermentation to acetone, ethanol, butanol, and polyhydroxyalkanoates from several Ulva species has already been demonstrated …”
Section: Introductionmentioning
confidence: 76%
“…Relocating seaweeds from high nutrient concentrations to low nutrient concentrations could further enhance the carbohydrate content of the subjected seaweeds. In this regard and while relocation of seaweed biomass may be technically challenging or cost-ineffective on large scales (see Korzen et al 2015), exposures back to low nutrient levels enhanced significantly the seaweed carbohydrate content. There is also an additional environmental benefit and ecosystem service of high value to be evaluated when integrating algal and finfish cultures.…”
Section: Discussionmentioning
confidence: 99%
“…dried biomass contained 16 to 22% of its dried biomass as TRS (total Reducing Sugars), and TRS showed a conversion rate of 30% to ethanol upon fermentation. The feasibility of producing Ulva feedstock in outdoor land-based cultivation for bioethanol production has been investigated and economic analyses have been conducted [ 96 , 97 , 98 , 99 ]. A long-term research program has shown that outdoor ponds of 1000 m 2 can produce 10 tons of Ulva biomass (DW) per year which can generate about 730 L of ethanol [ 96 , 98 ].…”
Section: Ulva Biomass Composition and Its Potential Applicat...mentioning
confidence: 99%